2018
DOI: 10.1167/iovs.18-23960
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Structural Changes Correlate With Neovascular Activity in Neovascular Age Related Macular Degeneration

Abstract: Choroidal thickness and CVI significantly increased with active disease in nAMD eyes. Changes in choroidal thickness may predict CNV development or recurrence before they are otherwise evident clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 24 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…This result was interpreted as a sign of subclinical choroidal ischemia, which may precede the typical manifestations of AMD such as CNV. Another recent study described an increase of choroidal vascularity in eyes with AMD before development or reactivation of CNV [26]. Therefore, serial CVI measurement might be a useful tool to predict the development or reactivation of CNV in patients with AMD.…”
Section: Discussionmentioning
confidence: 97%
“…This result was interpreted as a sign of subclinical choroidal ischemia, which may precede the typical manifestations of AMD such as CNV. Another recent study described an increase of choroidal vascularity in eyes with AMD before development or reactivation of CNV [26]. Therefore, serial CVI measurement might be a useful tool to predict the development or reactivation of CNV in patients with AMD.…”
Section: Discussionmentioning
confidence: 97%
“…These results may suggest a stromal replacement of the choroidal vessels occurring in the setting of GA [59]. Invernizzi and colleagues performed a longitudinal analysis to correlate changes in CT and CVI with disease activity in eyes with neovascular AMD [60].…”
Section: In Age-related Macular Degenerationmentioning
confidence: 99%
“…Of note, only type 1 lesions demonstrated statistically significant modifications in CVI from the inactive to the active form of the disease. The authors argued that these results may be secondary to the fact that type 1 CNV is located beneath the RPE, which may increase the diffusion of inflammatory mediators within the choroid [60].…”
Section: In Age-related Macular Degenerationmentioning
confidence: 99%
“…One hypothesis is that ischemia in areas of choriocapillary flow reductions/flow voids dictates the location in which neovascular lesions develop. Choroidal thickness measurements in neovascular AMD have been inconsistent; some groups report eyes with choroidal neovascularization have thinner choroids than age-matched healthy controls (Chung et al 2011), while the development of active or recurrent exudative neovascular AMD has also been associated with increased subfoveal choroidal thickness (Bouteleux et al 2019;Invernizzi et al 2018). This increased choroidal thickness has been shown to be accompanied by an increase in the choroidal vascularity index (Invernizzi et al 2018), suggesting the change may be due to neovascularization within the choroid rather than edematous thickening.…”
Section: Changes In the Choroid In Late Amdmentioning
confidence: 99%
“…Choroidal thickness measurements in neovascular AMD have been inconsistent; some groups report eyes with choroidal neovascularization have thinner choroids than age-matched healthy controls (Chung et al 2011), while the development of active or recurrent exudative neovascular AMD has also been associated with increased subfoveal choroidal thickness (Bouteleux et al 2019;Invernizzi et al 2018). This increased choroidal thickness has been shown to be accompanied by an increase in the choroidal vascularity index (Invernizzi et al 2018), suggesting the change may be due to neovascularization within the choroid rather than edematous thickening. Several studies have demonstrated that OCTA can accurately identify choroidal neovascularization (de Carlo et al 2015;Jia et al 2014Jia et al , 2015, offering a clear depiction of the CNV net (Fig.…”
Section: Changes In the Choroid In Late Amdmentioning
confidence: 99%